SISTEM INFORMASI PEMESANAN RUANGAN MEETING BERBASIS WEB APP MENGUNAKAN FRAMEWORK CODEIGNITER PADA PT BARATA INDONESIA – CILEGON, BANTEN - Khasan Asrori; Ely Nuryani (Program Studi Sistem Informasi, Universitas Banten Jaya, 2021)
Along with the development of the technology field at the company PT. Barata Indonesia, needs support to assist organizational activities, such as in ordering meeting rooms. Currently, information of meeting rooms availability and ordering at PT. Barata Indonesia still hasn't used technology so the process of ordering a meeting room is by contacting the room admin to ask about the availability of the place to be booked. This is less effective because the customer cannot know directly which room can be used for meetings and according to the capacity of the person. Therefore, this application is made to facilitate ordering meeting rooms at the company. The development of this meeting room reservation information system uses the SDLC Waterfall method which aims to simplify and speed up information access. The development of this Meeting Room Reservation Information System uses the CodeIgniter 3 Framework, which has 2 (two) interfaces, namely FrondEnd, which is the start page of the web application that is displayed for visitors and BackEnd is the admin page to process the required information data sources. The results of the system trial show that the application of the Meeting Room Booking Information System can provide more flexible information.